Meeting the Europe 2020 Strategy sustainable development guidelines by Poland - Witkowska-Dąbrowska, Mirosława; Świdyńska, Natalia; Napiórkowska-Baryła, Agnieszka (Wykonanie wytycznych strategii ,,Europa 2020” w zakresie zrównoważonego rozwoju w Polsce, 2019)
Many documents produced by the EU, including the Europe 2020 Strategy, advocate the assumption that the European Union member states will strive to achieve sustainable development, which therefore needs to be measured with comparable parameters. The research objective was to evaluate sustainable growth indicators in Poland against the background of the same indicators in the European Union, and to ‘estimate’ chances to achieve the objectives set in the Europe 2020 Strategy. Two hypotheses were put forward in the study: a large number of indicators analysed by the Main Statistical Office in Poland allows forecasting the achievement of Poland’s objectives adopted in the Strategy; the most difficult to achieve will be the goal of financing research and development. In Poland, not all the changes were beneficial. The EU as a whole has the chance to approximate to the set value of the indicators. Both hypotheses were verified
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 103-116
Keywords: strategy; sustainable development; indicators; strategia; zrównoważony rozwój; wskaźniki